2019
DOI: 10.1111/cmi.13035
|View full text |Cite
|
Sign up to set email alerts
|

Celiac disease‐associated Neisseria flavescens decreases mitochondrial respiration in CaCo‐2 epithelial cells: Impact of Lactobacillus paracasei CBA L74 on bacterial‐induced cellular imbalance

Abstract: We previously identified a Neisseria flavescens strain in the duodenum of celiac disease (CD) patients that induced immune inflammation in ex vivo duodenal mucosal explants and in CaCo‐2 cells. We also found that vesicular trafficking was delayed after the CD‐immunogenic P31‐43 gliadin peptide‐entered CaCo‐2 cells and that Lactobacillus paracasei CBA L74 (L. paracasei‐CBA) supernatant reduced peptide entry. In this study, we evaluated if metabolism and trafficking was altered in CD‐N. flavescens‐infected CaCo‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Furthermore, CD-Nf induced inflammatory phenotypes in ex-vivo mucosal explants, and in both human and murine DCs [25] (Figure 2). We also observed statistically significant lower mitochondrial activity, accompanied by lower ATP production and by higher oxidative stress in CD-Nfinfected Caco-2 cells than in untreated Caco-2 cells [62]. Based on the aforementioned metabolic alterations, we hypothesized that the CD-Nf that we isolated from the duodenum of CD patients, could contribute to the pathogenesis of CD or to disease exacerbation.…”
Section: Host Immune-microbiota Interactionmentioning
confidence: 80%
See 1 more Smart Citation
“…Furthermore, CD-Nf induced inflammatory phenotypes in ex-vivo mucosal explants, and in both human and murine DCs [25] (Figure 2). We also observed statistically significant lower mitochondrial activity, accompanied by lower ATP production and by higher oxidative stress in CD-Nfinfected Caco-2 cells than in untreated Caco-2 cells [62]. Based on the aforementioned metabolic alterations, we hypothesized that the CD-Nf that we isolated from the duodenum of CD patients, could contribute to the pathogenesis of CD or to disease exacerbation.…”
Section: Host Immune-microbiota Interactionmentioning
confidence: 80%
“…Numerous studies focused on the putative causal role of specific bacterial groups in the pathogenesis of CD [18,25,27,54,[60][61][62][63][64][65][66]. Below, we summarize results that suggest the putative pathogenic role of specific microbes in CD.…”
Section: The Putative Pathogenic Role Of Cd-associated Dysbiosismentioning
confidence: 99%
“…The CD-associated Neisseria flavescens was able in inducing inflammation in dendritic cells, in ex-vivo duodenal mucosa explants of healthy controls and in CaCo-2 cells [4]. In the latter cellular model, the CD-associated N. flavescens also induced significant metabolic imbalance by decreasing mitochondrial respiration [5]. Opposite to the dysbiotic profile that we found in a-CD patients, both oral and duodenal microbiome recovered in GFD patients.…”
Section: Resultsmentioning
confidence: 54%
“…The a-CD-associated N. flavescens showed pro-inflammatory activities in vitro, suggesting its potential involvement in the CD-related inflammation [4]. Moreover, we found that the a-CD-associated N. flavescens affected mitochondrial respiration in CaCo-2 epithelial cells [5]. Next, we investigated the oropharyngeal microbiome in CD patients and controls to evaluate whether this niche shared microbial composition with the duodenum [6].…”
Section: Introductionmentioning
confidence: 84%
“…Most of the probiotics on the market are dairy based, although cereals are becoming a viable alternative, as they bypass problems such as lactose intolerance or impact on cholesterolaemia ( Prado et al., 2008 ). Several studies have demonstrated the feasibility of lactic fermentation on cereals and the probiotic effect that fermented cereals can exert ( Sarno et al., 2014 ; Gallo et al., 2018 , 2019a ; Salameh et al., 2019 ; Labruna et al., 2019 ). The advantages offered by cereals therefore represent a boost for the design of new cereals-based foods and ingredients.…”
Section: Introductionmentioning
confidence: 99%